Design of Student Worksheets for The Collision Material to Develop Analytical Thinking Skills - Hidayah, Husnul; Imtinan, Nisrina; Linuwih, Suharto; Aji, Mahardika Prasetya (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2020)
Student worksheets are used as a learning resource that is concise and practical. The design of student worksheets that is concise and practical tends to be low in developing the stages of thinking processes. Physics learning that studies natural behavior always involves analytical thinking. The development of student worksheets based on analytical thinking design is the important goal in this study. Three stages are used to develop student worksheets with an analytical thinking design, that are differentiating, organizing, and attributing. Student worksheets design with the development of analytical thinking has been generated for momentum material. The differentiating stage includes identifying the quantity of moving object, defining the amount of momentum and estimating the velocity before and after the collision. The organizing stage includes the activities of analyzing and relating the momentum quantity to the collision phenomenon. While the attributing stage includes the activities of deducing the relation between momentum quantity and the collision phenomenon, also evaluating the law of conservation of linear momentum of a collision. The results of student worksheets validation obtained a percentage of 92.9%, so this learning resource is in a highly valid criteria. The design of student worksheets that develop analytical thinking skills can form the basis and support higher thinking skills.